Strategies for Accreditation Management Towards an Excellent Rating - Puri, Dian Ratna; Lubis, Wildansyah; Rangkuti, Irsan (Journal La Sociale, 2024)
This article explores the comprehensive strategies implemented by MTs. Swasta Nurul Iman Tanjung Morawa to achieve educational excellence and accreditation. The school's approach encompasses leadership and vision, curriculum enhancement, faculty development, student engagement, community involvement, infrastructure improvement, quality assurance, data-driven decision making, extracurricular activities, and partnerships. Leadership provides strategic direction, aligning goals with accreditation standards. Curriculum enhancement ensures relevance and quality of educational experiences. Faculty development fosters professional growth through training and support. Student engagement promotes holistic development and a supportive learning community. Community involvement leverages stakeholder support and resources. Infrastructure improvements create conducive learning environments. A rigorous quality assurance system monitors and enhances educational practices, informed by data-driven decision making. Extracurricular activities enrich student experiences beyond academics. Partnerships with stakeholders and networks enhance resources and professional development. These initiatives underscore MTs. Swasta Nurul Iman Tanjung Morawa's commitment to educational excellence, preparing students for future challenges and fostering a culture of continuous improvement and community impact.